2018
DOI: 10.1002/asia.201800582
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release of RNAi Molecules by Tunable Supramolecular Hydrogel Carriers

Abstract: Local, sustained release and presentation of RNAi therapeutics can be achieved with hydrogel delivery systems. Here we show the development of a supramolecular hydrogel into a local RNAi delivery system. By careful material design, two simple but effective strategies are introduced to obtain controlled release of two classes of RNAi therapeutics, that is, microRNA and antimiR. It was shown that the release of microRNA could be regulated using cholesterol-modification for interaction with the supramolecular hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…The former constitute a highly dynamic transient network that has been exploited for the release of growth factors, anti-cancer drugs, therapeutic siRNA and MRIcontrast agents. [16][17][18][19][20] The chain-extended UPy-hydrogel based on poly(ethylene glycol) (UPy-PEG) reported by Guo et al exhibited shape memory behavior after more than 300% strain while incorporating a water weight fraction up to 0.85. Furthermore, a UPy-PEG/gelatin blend was processable with electrospinning and the resulting mesh supported growth of a healthy monolayer of kidney epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…The former constitute a highly dynamic transient network that has been exploited for the release of growth factors, anti-cancer drugs, therapeutic siRNA and MRIcontrast agents. [16][17][18][19][20] The chain-extended UPy-hydrogel based on poly(ethylene glycol) (UPy-PEG) reported by Guo et al exhibited shape memory behavior after more than 300% strain while incorporating a water weight fraction up to 0.85. Furthermore, a UPy-PEG/gelatin blend was processable with electrospinning and the resulting mesh supported growth of a healthy monolayer of kidney epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…These self-assembled systems are only as strong as their weakest link; future supramolecular systems need to confirm and quantitatively measure that this weakest link is not the supramolecular host-guest interaction. 13 C NMR spectra were recorded on a Varian Mercury (400 MHz for 1 H NMR and 100 MHz for 13 C NMR) spectrometer at 298 K. Chemical shifts are reported in ppm downfield from TMS at room temperature. Abbreviations used for splitting patterns are s, singlet; t, triplet; q, quartet; m, multiplet; and br, broad.…”
Section: Discussionmentioning
confidence: 99%
“…[10] In the Dankers and Meijer laboratories, it was shown that the ureido-pyrimidinone (UPy) moiety coordinated the dynamic presentation of guests on water soluble host fibers. [11] Furthermore, in the gel regime, the same water soluble supramolecular material has proven to be functional for growth factors [12] and RNAi delivery [13] as well as guided MRI. [14] While the supramolecular incorporation of cell-adhesion signals suggests a perfect match to the continuously adapting cellular demands during development, there is a crucial system property to take into account: the balance of cell-ligand interaction versus ligand-material interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For some metabolic modulators that regulate the ECM, a more sustained release is required. Many strategies are available to induce a sustained release, ranging from coupling, host-guest chemistry to encapsulating in cellulose capsules ( Bakker et al, 2018a ; Bakker et al, 2018b ; Sun et al, 2019 ). Furthermore, many different intelligent biomaterials have been developed that respond to the environment, including cues such as pH, reactive oxygen species (ROS), MMPs, or even mechanotransduction.…”
Section: A Toolbox For (Bio)materials Scientists To Influence Metabolism and Thereby Affect Ecmmentioning
confidence: 99%